The students’ reflective writing manifestation of reader-response literary analysis - R. Bunga Febriani (Universitas Islam Sultan Agung, 2019)
This article presents reflective writing manifestation in Reader-response literary analysis. The article is aimed at finding out how the reflective writing is manifested in the students’ Reader-response of literary analysis. The writer carried out the study by analyzing the students’ portfolio documents of their reflective essays responding to three literary works. Fourteen students enrolling Literary Criticism Subject at a private university in West Java took part in the present research. Literary Criticism subject was chosen as the object of the current study, considering that the students in enrolling the subject were not merely introduced to literature, but also were led to be able to evaluate, describe, and analyze literary works. The study revealed some findings. Firstly, Reader-response prompts were helpful in giving aids to the students that they give the students idea how to write down their ideas and thoughts in minds. However, as the second finding, most students tend to keep their focus on the feeling section. Some of them were proven to be more critical by questioning things happened in the stories, yet they still had no idea how to analyze and evaluate the questions they had. The last finding, the writer noticed that none of the students relate their reflective essays to relevant literature to support their opinion. The writer considered that this occurred due to their lack of knowledge and practice of critical thinking and critical writing.